Electron-irradiation promoted exchange reaction as a tool for surface engineering and chemical lithography - Terfort, Andreas; Zharnikov, Michael (Advanced materials interfaces, 2021)
Self-assembled monolayers (SAMs) can serve as versatile resist/template materials for surface engineering and electron beam lithography (EBL), making possible a new type of lateral patterning: chemical lithography (CL). Whereas CL has been well established for aromatic SAMs, it is hardly possible for aliphatic monolayers, because of extensive irradiation-induced damage excluding selective modification of specific chemical groups. Turning this drawback into an advantage, the irradiation-promoted exchange reaction approach is developed, which is described in detail in the present review. The key idea of the approach is tuning the extent of the exchange reaction between a primary aliphatic SAM covering the substrate and a potential molecular substituent, which is capable of building a SAM on the same support, by electron irradiation. The major advantages of the approach are low irradiation doses (≤1 mC cm−2) and flexible choice of SAM-forming molecules, with a broad pool available commercially. Consequently, a large variety of binary SAMs with controlled compositions can be prepared and, in combination with EBL, complex chemical patterns can be fabricated, serving in particular as templates for subsequent area-selective chemical reactions, surface-initiated polymerization, attachment of nanoparticles, non-specific and specific proteins adsorption, and growth of 3D DNA nanostructures.
Gesehen am 17.04.2023